A New Species of Sarcophaga Meigen 1826 ( Diptera: Sarcophagidae) From Iraq - Mawlood, N. A. K (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This research includes a detailed morphological description of the Sarcophaga dialensis sp . nov . in Iraq . Many morphological characters are used in identification especially chaetotaxy and male genitalia .Locality records , data of collection and host plant were mentioned.